Hemangiomatosis of the spleen in a patient with Klippel-Trénaunay syndrome - S Dekeyzer; B Houthoofd; A De Potter; M Van Bockstal; P Smeets; D Vogelaers (Journal of the Belgian Society of Radiology, 2013)
Klippel-Trénaunay syndrome is a rare disorder characterized by a triad of port-wine stains, varicose veins, and bony and soft tissue hypertrophy usually involving an extremity. Visceral involvement in Klippel-Trénaunay syndrome is rare, but has been described in the colon, small bowel, bladder, kidney, spleen, liver, mediastinum and brain. In this paper we present the case of a 45-year-old woman with Klippel-Trénaunay syndrome in whom routine physical examination unexpectedly revealed the presence of a left upper quadrant mass. Abdominal US, contrast enhanced CT and whole-body PET-CT demonstrated multiple large cystic lesions within a massively enlarged spleen. Based on the clinical history and imaging findings diffuse hemangiomatosis of the spleen was suspected. This diagnosis was confirmed by pathologic examination after splenectomy.